Professors and Public Intellectuals in the Information Age. - Brantlinger, Patrick (Shofar: An Interdisciplinary Journal of Jewish Studies)
This essay examines relations among public intellectuals, professors, and information technology. It ponders the epistemological consequences of substituting computerized information especially for forms of critique expected of public intellectuals. It also surveys arguments about the speeding-up and increasing power of computers, especially in regard to higher education. It concludes that there is little if any reason to be optimistic about futures of either public intellectuals or professors under the relentless impact of the computerization and commodification of knowledge and education.